2019
DOI: 10.1002/dta.2548
|View full text |Cite
|
Sign up to set email alerts
|

Methionine329 in human serum albumin: A novel target for alkylation by sulfur mustard

Abstract: Exposure to the vesicant sulfur mustard (SM) may lead to erythema and blistering.Toxicity of SM is hypothesized due to the alkylation of DNA bases and nucleophilic amino acid side chains in proteins (adducts) by forming the hydroxyethylthioethyl (HETE) moiety. Despite its prohibition by the chemical weapons convention, SM still represents a serious threat to military personnel and civilians. Therefore, development and improvement of forensic analytical methods for the verification of SM exposure is of high int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
0
18
1
Order By: Relevance
“…While secondary markers are not unambiguous for identification but able to support identifications based on primary ones, data has to be reported from at least one primary biomarker. For the identification of SM in human plasma samples, the primary biomarkers are HETE-CP (from HSA), HETE-CPF (from HSA), N1/N3-HETE-His (from HSA and Globin), and other protein-or amino acid-adducts (e.g., AE 230 (-HETE) VSKL from HSA [12] and LGM 329 (-HETE) F from HSA, [9]), while the secondary marker for SM is thiodiglycol [41]. Our aim was to develop methods for the analysis and identification of HETETE-CP and HETETE-CPF as primary biomarkers of Q in plasma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While secondary markers are not unambiguous for identification but able to support identifications based on primary ones, data has to be reported from at least one primary biomarker. For the identification of SM in human plasma samples, the primary biomarkers are HETE-CP (from HSA), HETE-CPF (from HSA), N1/N3-HETE-His (from HSA and Globin), and other protein-or amino acid-adducts (e.g., AE 230 (-HETE) VSKL from HSA [12] and LGM 329 (-HETE) F from HSA, [9]), while the secondary marker for SM is thiodiglycol [41]. Our aim was to develop methods for the analysis and identification of HETETE-CP and HETETE-CPF as primary biomarkers of Q in plasma.…”
Section: Resultsmentioning
confidence: 99%
“…Q and SM competed for the thiol groups of a limited amount of Cys 34 applied as neat HSA instead of plasma to minimize any side reactions with other plasma proteins. As numerous amino acids of HSA are expected to be prone to alkylation as exemplarily shown for Glu 230 [12] and Met 329 [9], a low HSA concentration was applied. After incubation, samples were subjected to pronase-mediated proteolysis to monitor HETE-CP and HETETE-CP simultaneously as measures of their respective HSA-adducts.…”
Section: Alkylationmentioning
confidence: 99%
See 1 more Smart Citation
“…After alkylation, a Met sulfonium ion is formed containing a permanent positive charge at the sulfur atom (Kramer and Deming 2012) which may cause conformational changes in the protein tertiary structure or may even cause disturbance of the protein secondary structure (Kramer and Deming 2013). Recently, it was shown that Met residues may also be alkylated by SM as proven for Met 329 in human serum albumin (Siegert et al 2019).…”
Section: Identification Of Alkylated Met 70 and Met 179 After Sm Treatment Of Rmck And Correlation To Enzyme Activitymentioning
confidence: 99%
“…Treatment of CK with the alkylating chemical warfare agent sulfur mustard (SM) resulted in the formation of the specific hydroxyethylthioethyl-(HETE)-moiety at Cys 283 (Lüling et al 2021;Steinritz et al 2021) but its effect on enzyme activity has not been addressed so far. This was investigated in the present study with particular focus on Cys 283 but also on reactive Met residues, that in principle might also be essential for the activity of certain enzymes (Rogers et al 1976) and were shown to be a potential target of alkylation by SM (Siegert et al 2019).…”
Section: Introductionmentioning
confidence: 99%